2021
DOI: 10.1155/2021/9963999
|View full text |Cite
|
Sign up to set email alerts
|

Precision Measurement for Industry 4.0 Standards towards Solid Waste Classification through Enhanced Imaging Sensors and Deep Learning Model

Abstract: Achievement of precision measurement is highly desired in a current industrial revolution where a significant increase in living standards increased municipal solid waste. The current industry 4.0 standards require accurate and efficient edge computing sensors towards solid waste classification. Thus, if waste is not managed properly, it would bring about an adverse impact on health, the economy, and the global environment. All stakeholders need to realize their roles and responsibilities for solid waste gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In 1990, Picard et al 27 found that the division ratio of the training set, validation set, and training set, although not mandatory but has a certain impact on the evaluation performance, as can be seen from a large number of training studies on neural networks in recent years, most researchers have used a ratio of 80% for the training set and 20% for the rest. 30,31 For BP-ANN and its derivative models, this paper uses the ratio of the training set, validation set, and test set 8:1:1 to divide them, and for other neural network models, this paper uses the ratio of the training set to test set 8:2 to divide them.…”
Section: Description Of the Poa-bp Methodology And Comparison Of Trai...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, Picard et al 27 found that the division ratio of the training set, validation set, and training set, although not mandatory but has a certain impact on the evaluation performance, as can be seen from a large number of training studies on neural networks in recent years, most researchers have used a ratio of 80% for the training set and 20% for the rest. 30,31 For BP-ANN and its derivative models, this paper uses the ratio of the training set, validation set, and test set 8:1:1 to divide them, and for other neural network models, this paper uses the ratio of the training set to test set 8:2 to divide them.…”
Section: Description Of the Poa-bp Methodology And Comparison Of Trai...mentioning
confidence: 99%
“…From researchers’ studies, 30,31 it can be seen that the number of layers of the hidden layer structure of the neural network affects the prediction accuracy of the overall model as well as the computing time, especially for the prediction of the processing parameters of a very complex mechanical structure such as a pure electric vehicle power pack, it is more necessary to increase the number of layers of the structure of the neural network to improve the accuracy of the prediction, but too many layers will increase the difficulty of the calculation. This paper set up a single input layer with an output layer and increase the single hidden layer in order according to a sequence of equal differences with a tolerance of 1.…”
Section: Description Of the Poa-bp Methodology And Comparison Of Trai...mentioning
confidence: 99%
“…To ensure the success of recycling, it is essential to separate and manage waste efficiently and properly. Computational complexity in the classification of non-organic waste is directly related to the performance of peripheral computing devices [11]. Existing research in waste classification has been carried out using CNN architectures, such as AlexNet, which contains a large number of parameters and requires a great many operations to classify a single image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the class allocation is skewed, there is a drawback in the fundamental "majority voting" classification [18]. That is, examples of a more regular class tend to dominate the new example prediction because they are common among k neighbors, because they are numerous [19].…”
Section: Classificationmentioning
confidence: 99%